Early primary care physician contact and health service utilisation in a large sample of recently released ex-prisoners in Australia: prospective cohort study. Issue 6 (11th June 2015) - Young, Jesse T; Arnold-Reed, Diane; Preen, David; Bulsara, Max; Lennox, Nick; Kinner, Stuart A
Abstract : Objective: To describe the association between ex-prisoner primary care physician contact within 1 month of prison release and health service utilisation in the 6 months following release. Design: A cohort from the Passports study with a mean follow-up of 219 (±44) days postrelease. Associations were assessed using a multivariate Andersen-Gill model, controlling for a range of other factors. Setting: Face-to-face, baseline interviews were conducted in a sample of prisoners within 6 weeks of expected release from seven prisons in Queensland, Australia, from 2008 to 2010, with telephone follow-up interviews 1, 3 and 6 months postrelease. Participants: From an original population-based sample of 1325 sentenced adult (≥18 years) prisoners, 478 participants were excluded due to not being released from prison during follow-up (n=7, 0.5%), loss to follow-up (n=257, 19.4%), or lacking exposure data (n=214, 16.2%). A total of 847 (63.9%) participants were included in the analyses. Exposure: Primary care physician contact within 1 month of follow-up as a dichotomous measure. Main outcome measures: Adjusted time-to-event hazard rates for hospital, mental health, alcohol and other drug and subsequent primary care physician service utilisations assessed as multiple failure time-interval data. Results: Primary care physician contact prevalence within 1 month of follow-up was 46.5%. One-month primary care physician contact was positively associated with hospital (adjusted HR (AHR)=2.07; 95% CI 1.39 to 3.09), mental health (AHR=1.65; 95% CI 1.24 to 2.19), alcohol and other drug (AHR=1.48; 95% CI 1.15 to 1.90) and subsequent primary care physician service utilisation (AHR=1.47; 95% CI 1.26 to 1.72) over 6 months of follow-up. Conclusions: Engagement with primary care physician services soon after prison release increases health service utilisation during the critical community transition period for ex-prisoners. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12608000232336).